The socio - Spatial Accumulation of cement corporations : the reproduction of Absolute Space, Monumentalization of Kiai, and Compartmentalization of Counter Space in Northern Kendeng, Central Java Indonesia - Fuad Faizi (Program Pascasarjana Universitas Islam Negeri Sunan Kalijaga, 2022)
et,1/ yna, c.1